Linear functionals connected with strong double cesaro summability - Nuray, Fatih; Pancaroğlu Akın, Nimet (My University, 2019)
D. Borwein characterized linear functionals on the normed linear spaces wp and Wp. In this paper we extend his results by presenting definitions for the double strong Cesaro mean. Using these new notions of strongly p-Cesaro summable double sequence and strongly p-Cesaro summable bivariate function we present extensions of D. Borwein’s results.
Keywords: Double Sequence; Measurable Function; Bivariate Function; Cesaro Summable Function